2006
DOI: 10.1080/09553000600643516
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral leukocyte response to oncological radiotherapy: Expression of heat shock proteins

Abstract: Radiotherapy downregulates hsp27 and 70i, which would enhance radiosensitivity. HSP content prior to treatment is suggested as a prognostic biomarker for radiation tolerance, with circulating leukocytes as biosensors. HSP-Ab may be biomarkers of tumor disease, but do not seem to be involved in the morbidity of acute post-radiotherapy disease, which is closely related to the volumes irradiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, this apparent difference was not statistically significant ( P >0.05) and therefore does not seem to explain completely the mechanism by which the CC/CG genotype reduced mortality risk in that study. In another study, Guisasola et al [19] reported that radiotherapy caused HSP27 downregulation, to the greatest extent in patients with the largest irradiated volumes, and led to decreased intracellular HSP levels. Thus, we hypothesize that patients carrying the rs2868371 CC genotype may have less HSP27 downregulation than those carrying other genotypes after radiotherapy and therefore may overexpress HSP27.…”
Section: Discussionmentioning
confidence: 99%
“…However, this apparent difference was not statistically significant ( P >0.05) and therefore does not seem to explain completely the mechanism by which the CC/CG genotype reduced mortality risk in that study. In another study, Guisasola et al [19] reported that radiotherapy caused HSP27 downregulation, to the greatest extent in patients with the largest irradiated volumes, and led to decreased intracellular HSP levels. Thus, we hypothesize that patients carrying the rs2868371 CC genotype may have less HSP27 downregulation than those carrying other genotypes after radiotherapy and therefore may overexpress HSP27.…”
Section: Discussionmentioning
confidence: 99%
“…The Hsp27 level prior to treatment was suggested as a prognostic biomarker for radiation tolerance. NSCLC patients with the greatest interleukocyte Hsp27 levels before treatment suffered more severe acute radiation morbidity (Guisasola et al 2006 ). Lopez Guerra et al investigated the association of the HSPB1 rs2868371 polymorphism with radiation-induced esophageal toxicity in radio(chemo)therapy treated NSCLC patients.…”
Section: Hspb1 Variants In Lung Cancermentioning
confidence: 98%